2016
DOI: 10.1007/s40484-016-0063-4
|View full text |Cite
|
Sign up to set email alerts
|

Integrative clustering methods of multi‐omics data for molecule‐based cancer classifications

Abstract: One goal of precise oncology is to re-classify cancer based on molecular features rather than its tissue origin. Integrative clustering of large-scale multi-omics data is an important way for molecule-based cancer classification. The data heterogeneity and the complexity of inter-omics variations are two major challenges for the integrative clustering analysis. According to the different strategies to deal with these difficulties, we summarized the clustering methods as three major categories: direct integrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 93 publications
(109 reference statements)
0
36
0
Order By: Relevance
“…Pavel et al (2016) used a fuzzy logic modeling framework (Xu et al 2008) to integrate multiple types of omics data with expert curated biological rules for identification of cancer drivers and to infer patientspecific gene activity. To deal with sample heterogeneity, Wang and Gu (2016) have proposed three clustering categories, direct integrative clustering, clustering of clusters and regulatory integrative clustering. Nibbe et al (2010) demonstrated that integration of complementary data sources (transcriptomic and proteomic data) using a 'proteomics-first' approach can enhance discovery of candidate sub-networks in cancer.…”
Section: Tools Available For Integration Of Multi-omics Datamentioning
confidence: 99%
“…Pavel et al (2016) used a fuzzy logic modeling framework (Xu et al 2008) to integrate multiple types of omics data with expert curated biological rules for identification of cancer drivers and to infer patientspecific gene activity. To deal with sample heterogeneity, Wang and Gu (2016) have proposed three clustering categories, direct integrative clustering, clustering of clusters and regulatory integrative clustering. Nibbe et al (2010) demonstrated that integration of complementary data sources (transcriptomic and proteomic data) using a 'proteomics-first' approach can enhance discovery of candidate sub-networks in cancer.…”
Section: Tools Available For Integration Of Multi-omics Datamentioning
confidence: 99%
“…Many clustering methods have been specifically developed to analyse multi-omics data. Several authors provide full reviews and benchmarks [9][10][11]. In particular, Wang and Gu [9] suggest the following typology: i) direct integrative clustering, consisting in a preprocessing of the original data set before concatenation into a single data set ready for some standard clustering analysis [12,13]; ii) regulatory integrative clustering, which are based on pathways [14]; iii) clustering of clusters, i.e., methods that take clustering made on different data sets and find a consensus [15,16].…”
Section: Multi-omicsmentioning
confidence: 99%
“…Several recent reviews discussed multi-omics integration. [10], [11] and [12] review methods for multiomics integration, and [13] review multi-omics clustering for cancer application. These reviews do not include a benchmark, and do not focus on multi-view clustering.…”
Section: Introductionmentioning
confidence: 99%